2021
DOI: 10.1186/s12872-021-02170-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a self-care educational intervention to improve self-care adherence among patients with chronic heart failure: a clustered randomized controlled trial in Northwest Ethiopia

Abstract: Background As the burden of cardiovascular disease increases in sub-Saharan Africa, there is a growing need for low-cost interventions to mitigate its impact. Providing self-care health education to patients with chronic heart failure (CHF) is recommended as an intervention to prevent complications, improve quality of life, and reduce financial burdens on fragile health systems. However, little is known about health education’s effectiveness at improving CHF self-management adherence in sub-Sah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 50 publications
5
42
0
3
Order By: Relevance
“…The goal of treatment for heart failure patients includes reducing symptoms and disease progression, prolonging survival, and improving quality of life. However, in Ethiopia, heart failure patent came after NYHA Class III and IV with limited knowledge about their disease, poor medication adherence practice, and transitional care (13)(14)(15). Furthermore, risky lifestyles such as smoking, a sedentary lifestyle, excessive salt intake, and alcohol consumption are most common in Ethiopia, which are predictors of unplanned hospitalizations for HF patients (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of treatment for heart failure patients includes reducing symptoms and disease progression, prolonging survival, and improving quality of life. However, in Ethiopia, heart failure patent came after NYHA Class III and IV with limited knowledge about their disease, poor medication adherence practice, and transitional care (13)(14)(15). Furthermore, risky lifestyles such as smoking, a sedentary lifestyle, excessive salt intake, and alcohol consumption are most common in Ethiopia, which are predictors of unplanned hospitalizations for HF patients (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of treatment for heart failure patients includes reducing symptoms and disease progression, prolonging survival, and improving quality of life. However, in Ethiopia, heart failure patent came after NYHA Class III and IV with limited knowledge about their disease, poor medication adherence practice, and transitional care (13-15).…”
Section: Introductionmentioning
confidence: 99%
“…3 A cluster randomised controlled trial conducted in Ethiopia concluded that self-care education significantly improved self-care adherence score among patients with HF. 4 The 2022 ACC/AHA/HFSA (American College of Cardiology/American Heart Association/Heart Failure Society of America) guidelines for the management of HF documented the role of interventions that aim to improve self-care knowledge and skill, and those that focus on enhancing medication adherence or reinforcing self-care with structured telephone support (STS) as being effective in patients with HF. In addition to improving HF selfcare significantly, such strategies also reduce the risk of HF-related hospitalisation, all-cause hospitalisation and all-cause mortality.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 3 A cluster randomised controlled trial conducted in Ethiopia concluded that self-care education significantly improved self-care adherence score among patients with HF. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation